Rome, China, and the Barbarians : Ethnographic Traditions and the Transformation of Empires - Ford, Randolph B. (Cambridge University Press, 2020)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Contents -- List of Maps -- Acknowledgments -- A Note to the Reader -- Introduction -- Comparative History of Greece-Rome and China -- Roman Late Antiquity and Early Medieval China: Brief Historical Background -- Primary Questions and Approaches -- Chapter 1 Ethnography in the Classical Age -- The Greco-Roman Ethnographic Tradition -- The Chinese Ethnographic Tradition -- Explanatory Paradigms in the Greco-Roman and Chinese Traditions -- Genealogy -- Geography, Climate, and Astrology -- History/Historical Change -- Conclusions -- Chapter 2 The Barbarian and Barbarian Antitheses -- The Term ''Barbarian'' and Its Chinese Equivalents -- Views of Barbarians in the Greco-Roman Tradition -- Views of Barbarian Others in Ancient China -- Conclusions -- Chapter 3 Ethnography in a Post-Classical Age: The Ethnographic Tradition in the Wars and the Jin shu 晉書 -- Perpetuation of the Barbarian Antithesis -- Ethnographic Continuity -- Ethnographic Paradigms -- Ethnography and the New Barbarians -- Conclusions -- Chapter 4 New Emperors and Ethnographic Clothes: The Representation of Barbarian Rulers -- Barbarian Figures in the Wars -- The Vandals -- The Goths -- Barbarian Figures in the Jin shu -- The Xiongnu 匈奴 Former Zhao 前 Dynasty -- The Jie 羯 Later Zhao 後 Dynasty -- The Särbi-Xianbei 卑 Former Yan 前燕 Dynasty -- The Ba-Di 巴氐 Chenghan 成漢 Dynasty -- The Xiongnu Xia 夏 Dynasty -- Conclusions -- Chapter 5 The Confluence of Ethnographic Discourse and Political Legitimacy: Rhetorical Arguments on the Legitimacy of Barbarian Kingdoms -- Political Legitimacy -- Speeches in Greco-Roman and Chinese Historiography -- Speeches in the Jin shu -- Speeches in the Wars -- Conclusions -- Conclusion -- Bibliography -- Primary Sources -- Secondary Sources -- Index.